Antimicrobial resistance guidance for 2021 data reporting. Issue 5 (19th May 2021) - (EFSA), European Food Safety Authority; Amore, Giusi; Beloeil, Pierre‐Alexandre; Bocca, Valentina; Fierro, Raquel Garcia; Gibin, Davide; Roman, Beatriz Guerra; Papanikolaou, Alexandra; Rizzi, Valentina; Stoicescu, Anca‐Violeta
Abstract : This technical report of the European Food Safety Authority (EFSA) presents guidance to reporting European Union (EU) Member States and non‐Member States in data transmission using extensible markup language (XML) data transfer covering the reporting of isolate‐based quantitative antimicrobial resistance and Whole Genome Sequencing (WGS) data. For data collection purposes, EFSA has created the Data Collection Framework (DCF) application. The present report provides data dictionaries to guide the reporting of information deriving from 2021 under the framework of Directive 2003/99/EC and Commission Implementing Decision 2020/1729/EC. The objective is to explain in detail the individual data elements that are included in the EFSA data models to be used for XML data transmission through the DCF. In particular, the data elements to be reported are explained, including information about the data type, a reference to the list of allowed terms and any additional business rule or requirement that may apply.